Probabilistic Distribution of Ultimate Pile Capacity Based on Pile Load Test Data - Al-Sheikh Ali, Anas Khaled Ali (Universiti Teknologi PETRONAS, 2017)
Soil bearing capacity is crucial to any foundation design process. It defines the max stress capacity a ground can sustain prior failing. Field pile tests were developed to verify the design process. From maintained load tests to Pile Dynamic Analysis, which essentially impose a specific load & record the further movement of the pile. Using appropriate interpretation methods, the designer can determine the true/actual bearing capacity based on a more realistic data such as pile-soil settlement. Afterwards, using the probabilistic inverse method, a probability density of frictional & point bearing will be constructed to be used in Bayesian’s statistical interpretation in order obtain the variation of Ultimate pile capacity along the boundaries of the tested piles. The probability distribution of ultimate pile capacity based on pile load test data will prove valuable in estimating design value of Ultimate bearing Capacity.